2017
DOI: 10.1167/iovs.16-20813
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Strengthening of the Human Cornea Induced by Nanoplatform-Based Transepithelial Riboflavin/UV-A Corneal Cross-Linking

Abstract: Citation: Labate C, Lombardo M, Lombardo G, De Santo MP. Biomechanical strengthening of the human cornea induced by nanoplatformbased transepithelial riboflavin/UV-A corneal cross-linking. Invest Ophthalmol Vis Sci. 2017;58:179-184. DOI: 10.1167/iovs.16-20813 PURPOSE. The purpose of this study was to investigate the biomechanical stiffening effect induced by nanoplatform-based transepithelial riboflavin/UV-A cross-linking protocol using atomic force microscopy (AFM).METHODS. Twelve eye bank donor human scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…In 2017, Lombardo and colleagues [73] showed that a nanotechnology-based riboflavin 0.1% solution was effective in enriching the anterior stroma with riboflavin through the intact epithelium of human donor corneas. Labate and colleagues [74] showed that TE-CXL using a modified Riboflavin with polymeric nanoparticles of cyclodextrin was effective to improve the biomechanical strength of donor human corneas.…”
Section: Future Perspectives Of Epithelium-on CXLmentioning
confidence: 99%
“…In 2017, Lombardo and colleagues [73] showed that a nanotechnology-based riboflavin 0.1% solution was effective in enriching the anterior stroma with riboflavin through the intact epithelium of human donor corneas. Labate and colleagues [74] showed that TE-CXL using a modified Riboflavin with polymeric nanoparticles of cyclodextrin was effective to improve the biomechanical strength of donor human corneas.…”
Section: Future Perspectives Of Epithelium-on CXLmentioning
confidence: 99%
“…We roughly sorted the measurement methods into two categories: the laboratory group includes the ex vivo assessment of corneal mechanical properties; whereas the clinical group (including both ex vivo and in vivo measurement results) encompasses techniques and methodologies that are intended for clinical applications. The laboratory group includes strip extensometry [24] , [28] , [86] , [87] , compression [88] , [89] , [90] , [91] , torsional rheometry [23] , corneal inflation [92] , [93] , [94] , [95] , [96] , speckle interferometry [97] , Terahertz spectroscopy [98] , atomic force microscopy (AFM) [99] , [100] , [101] , [102] ; while the clinical group includes tonometer [103] , [104] , [105] , [106] , ultrasound elastography (UE) [44] , [45] , [107] , wave-based OCE [22] , [47] , [48] , natural frequency (NF) OCE [49] , [50] , [51] , [108] . In studies marked with an asterisk (*), the shear modulus was originally reported, and a simple estimation was made by assuming Young’s modulus to be three times the shear modulus ( Eq.…”
Section: Corneal Anatomy and Biomechanicsmentioning
confidence: 99%
“…Fig. 3 compares different parameters that affect Young’s modulus, including strain values [24] , [28] , [86] , inflation pressures [92] , [93] , corneal regional variations [23] , [89] , [90] , [91] , [102] , [107] , aging [94] , [95] , [103] , corneal collagen crosslinking (CXL, Section 3.1 ) [28] , [86] , [87] , [90] , [99] , [100] , [101] , and refractive surgeries [28] , such as laser-assisted in situ keratomileusis (LASIK) and small incision lenticule extraction (SMILE). The in vivo measurement methods of human corneal biomechanics are discussed in detail in 4 , 5 .…”
Section: Corneal Anatomy and Biomechanicsmentioning
confidence: 99%
“…Nanomaterials such as polymeric nanoparticles and inorganic nanoparticles have also been developed to deliver RF to the corneal stroma. [21][22][23][24] As a class of hydrophobic materials, porous metal-organic frameworks (MOFs), especially nanosized MOF, has received much attention in recent years. [25][26][27] These are hybrid materials formed by self-assembly of polydentate bridging ligands and metal-connecting points, and can be obtained under relatively mild conditions as either crystalline or amorphous material.…”
Section: Introductionmentioning
confidence: 99%